2010
DOI: 10.1007/s00441-010-1017-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of Toll-like receptors in modulation of T cell responses

Abstract: The innate immune receptors, such as Toll-like receptors (TLRs), are intimately involved in the early sensing of invading microorganisms or their structural components. Engagement of TLRs with their ligands results in activation of several downstream intracellular pathways leading to activation of innate and adaptive immune system cells. It was initially thought that TLRs are primarily expressed by antigen-presenting cells (APCs), such as macrophages and dendritic cells, and that interactions between microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 87 publications
1
61
0
Order By: Relevance
“…ES-62-mediated suppression of the resultant IL-17 response therefore likely reflects not only the fact that TLRs can be expressed by most T cell subsets, but also the fact that TLR agonists (e.g., for TLR-3, -5, -7, and -9) can modulate Teff or Treg cell responses in the absence of antigen-presenting cells (for review, see ref. 27) and LPS/TLR-4 signaling can both induce and enhance IL-23-stimulated IL-17 release from Th17 cells differentiated in vitro (28).…”
Section: Discussionmentioning
confidence: 99%
“…ES-62-mediated suppression of the resultant IL-17 response therefore likely reflects not only the fact that TLRs can be expressed by most T cell subsets, but also the fact that TLR agonists (e.g., for TLR-3, -5, -7, and -9) can modulate Teff or Treg cell responses in the absence of antigen-presenting cells (for review, see ref. 27) and LPS/TLR-4 signaling can both induce and enhance IL-23-stimulated IL-17 release from Th17 cells differentiated in vitro (28).…”
Section: Discussionmentioning
confidence: 99%
“…It was initially thought that TLRs are preferentially expressed in innate immune cells, such as macrophages and dendritic cells, and activation of these cells by the interaction of a TLR and its ligand indirectly leads to the activation of cells of the adaptive immune system, especially T cells [3][4][5]. However, it is evident that some of TLRs are expressed in various subsets of ␣␤T cells as well as ␥␦T cells [6,7]. TLR1-9 are expressed in naïve T cells in mice while TLR1, 2, 3, 4, 5, 7 and 9 mRNA were detected in human peripheral blood T cells.…”
Section: Q2mentioning
confidence: 98%
“…In recent years, it has been observed that TLR expression is not restricted to the innate immune system. TLR were detected in B cells as well as in T cells and in their subpopulations [14,15,33]. Recent studies (as described below) identified TLR expression in cd T cells possibly playing an important role in early immune responses of cd T cells against different pathogens.…”
Section: Tlr Expression In T Cellsmentioning
confidence: 99%
“…TLR sense diverse pathogen-associated molecular patterns (PAMP), e.g., lipid-containing ligands, proteinaceous ligands, and nucleic acid ligands [12]. Besides their direct effects on cells of the innate immunity such as dendritic cells (DC) and NK cells, TLR have also been shown to co-stimulate TCR-activated human T cells [13][14][15]. In cd T cells, TLR1/TLR2, TLR2/TLR6, TLR3, and TLR5 ligands induce an enhanced production of cytokines and chemokines and an up-regulation of activation markers [16,17].…”
mentioning
confidence: 99%